2021
DOI: 10.1111/jcmm.16399
|View full text |Cite
|
Sign up to set email alerts
|

Tumour angiogenesis normalized by myo‐inositol trispyrophosphate alleviates hypoxia in the microenvironment and promotes antitumor immune response

Abstract: Pathologic angiogenesis directly responds to tumour hypoxia and controls the molecular/cellular composition of the tumour microenvironment, increasing both immune tolerance and stromal cooperation with tumour growth. Myo‐inositol‐trispyrophosphate (ITPP) provides a means to achieve stable normalization of angiogenesis. ITPP increases intratumour oxygen tension (pO2) and stabilizes vessel normalization through activation of endothelial Phosphatase‐and‐Tensin‐homologue (PTEN). Here, we show that the tumour reduc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 63 publications
0
17
0
Order By: Relevance
“…We have previously shown that ITPP shifts the oxygen dissociation curve downward, therefore increasing tissue oxygen delivery, increases oxygen delivery to hypoxic tumors 14 , and reduces HIF-1 expression by vascular endothelial cells 15 . This is accompanied by a potent anti-cancer effect in various tumor models in the mouse 14 , 16 . Moreover, we have recently shown that chronic ITPP treatment partially prevents post-myocardial infarction heart failure in the rat model 17 .…”
Section: Introductionmentioning
confidence: 99%
“…We have previously shown that ITPP shifts the oxygen dissociation curve downward, therefore increasing tissue oxygen delivery, increases oxygen delivery to hypoxic tumors 14 , and reduces HIF-1 expression by vascular endothelial cells 15 . This is accompanied by a potent anti-cancer effect in various tumor models in the mouse 14 , 16 . Moreover, we have recently shown that chronic ITPP treatment partially prevents post-myocardial infarction heart failure in the rat model 17 .…”
Section: Introductionmentioning
confidence: 99%
“…In addition, PI3K is activated by growth factors and angiogenesis inducers, such as vascular endothelial growth factor (VEGF) and angiopoietins, activates Akt or other targets, and induces HIF-1 and VEGF expression to regulate angiogenesis [40,41] . PTEN de cient endothelial cells showing increased excessive angiogenesis have been demonstrated in the vasculogenesis of tumors [42,43] . Akt regulates multiple downstream targets, including nitric oxide synthase (NOS), nuclear factor kappaB (NF-кB), glycogen synthase kinase 3(GSK-3), and Jun N-terminal kinase (JNK).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, it was shown that NK cell infiltration and its antitumor activity are impaired by the immune checkpoint molecule PD-L1, which is expressed under hypoxic conditions on endothelial cells in the tumor. The normalization of a hypoxic condition reverts immunosuppression into an antitumor immune response [42]. We may thus hypothesize that the same type of mechanism occurs in endometriosis lesions; nevertheless, further investigation is needed.…”
Section: Hypoxia-dependent Development Of Endometriosismentioning
confidence: 99%